Rupture of Ovarian Pregnancy in a Woman with Low Beta-hCG Levels. (11th November 2012) - Resta, Serena; Fuggetta, Eliana; D'Itri, Federica; Evangelista, Simona; Ticino, Adele; Porpora, Maria Grazia
Abstract : Background . Ovarian pregnancy is a rare form of ectopic pregnancy. It is often difficult to distinguish from tubal pregnancy, and diagnosis and management are frequently a challenge. Case . A 33-year-old nulligravida woman presented with light vaginal bleeding and bilateral lower quadrants abdominal pain. Beta-human chorionic gonadotropin (beta-hCG) level (592 mUI/mL) and clinical and ultrasound (US) findings were suspicious for tubal pregnancy. On the third day, despite beta-hCG decrease (364 mUI/mL), she complained of severe pain in the lower abdomen, and physical examination revealed abdominal rebound tenderness. US showed a large amount of fluid in the abdominal cavity. Because of the unstable clinical condition, emergency laparoscopy and resection of left ovarian ectopic pregnancy were performed. Histology confirmed ovarian gestation. Conclusion . This case shows that ectopic pregnancy rupture may occur despite low levels of beta-hCG. Hemoperitoneum is not contraindication to laparoscopy.